From Myths to Markets: Power, Institutions, and the Reification of Imagined Histories. (August 2019) - Carter, Elizabeth
Abstract: This article posits that institutionalized mythologies can create comparative production advantages. Myths shape collective identity, mobilize actors, and fundamentally reshape production dynamics. Myths are institutionalized in market rules, regulations and structures, leading to the reification of the myth. The myth functions as if it is true, not because it is true, but because it shapes the rules of production. Yet without the initial myth, specific production incentives—and even their institutional comparative advantages—would not exist. My theory integrates approaches from modernist historians ("imagined communities") and economic sociologists ("imagined futures") to explain how myths ("imagined histories") shape contemporary market outcomes, using the example of the French wine market. This argument contributes to the historical institutionalist approach, which focuses on the historical power dynamics between competing groups and the present-day social and market consequence of their institutionalized solutions. Résumé: Cet article affirme que les mythologies institutionnalisées créent parfois des avantages productifs comparatifs. Les mythes façonnent l'identité collective, mobilisent les acteurs et modifient en profondeur la dynamique de la production. Ils sont institutionnalisés dans les règles du marché, les réglementations et les structures, ce qui conduit à leur réification. Le mythe fonctionne comme s'il était vrai, non pas parce qu'il l'est, mais parce qu'il façonne les règles de production. Pourtant, sans le mythe initial, des incitations spécifiques à la production n'existeraient pas—tout comme leurs avantages comparatifs institutionnels. Ma théorie propose d'intégrer les approches des historiens modernistes (« communautés imaginées ») et des sociologues économiques (« futurs imaginés ») pour expliquer comment les mythes (« histoires imaginées ») façonnent les résultats du marché contemporain, en prenant l'exemple du marché du vin en France. Il s'agit de contribuer à une approche institutionnaliste historique centrée sur la dynamique de pouvoir entre des groupes rivaux et les conséquences sociales et marchandes de leurs solutions institutionnalisées. Zusammenfassung: Dieser Beitrag behauptet, dass institutionalisierte Mythen gelegentlich vergleichende Produktionsvorteile schaffen. Diese Mythen gestalten die kollektive Identität, mobilisieren die Handelnden und verändern nachhaltig Produktionsdynamiken. Ihre Verankerung in Marktregeln, Vorschriften und Strukturen führt zur Reifikation des Mythos. Letzterer mutiert zur Wahrheit, nicht weil er wahr ist, sondern weil er die Produktionsregeln mitgestaltet. Gleichzeitig kann festgestellt werden, dass es ohne einen Auslösungsmythos keine produktionsspezifischen Anreize geben würde – ebenso wenig wie ihre institutionellen komparativen Vorteile. Mein theoretischer Ansatz integriert die Überlegungen moderner Historiker (, , erfundene Gemeinschaften") und Wirtschaftssoziologen (, , erfundene Zukunft"), um die durch Mythen (, , erfundene Geschichten") geprägten zeitgenössischen Marktergebnisse zu erklären, z.B. den frz. Weinhandel. Diese Argumentation unterstützt den historischen Institutionsansatz, der sich auf historisch gewachsene Machtdynamiken zwischen konkurrierenden Gruppen und aktuellen sozialen sowie wirtschaftlichen Konsequenzen ihrer institutionalisierten Lösungen bezieht.